Trail runners: Neuromuscular and biomechanical insights - Bean, Rachel Christy Reid (Department of Human Biology, 2019)
Running is a popular recreational and competitive sport worldwide. Despite numerous proven health benefits associated with road running, the risk of sustaining a running-related injury (RRI) is extremely high. The cause of RRI is multifactorial and the result of running many kilometres on monotonous and mechanically stiff road surfaces has been suggested to increase the risk of sustaining an injury. Interestingly, this notion may be a key driving factor for the emergence and growing interest in, trail or 'off-road’ running. Research investigating road running has been well-described, whereas the impact of regular running on natural, dynamic trail surfaces on the musculoskeletal system has yet to be fully considered. Thus, this thesis sought to understand the trail running athlete, with particular focus on elucidating the clinical, biomechanical and neuromuscular consequences of habitual running training on off-road terrain. The present thesis begins with a comprehensive review of the literature. The aim of this chapter was to briefly describe the origins of trail running, explore the theoretical driving factors behind interest in trail running, and detail the current scientific understanding of trail running and the purported implications and benefits thereof. Gaps in the existing body of knowledge were highlighted, with recommendations for necessary future research. The first study aimed to describe clinical measures of dynamic stability in well-trained trail runners and contrast this group with age- and performance-matched road runners. All runners performed three clinical assessments: the Star Excursion Balance Test (SEBT), Unilateral Bridge Hold (UBH) and Single Leg Squat (SLS). No differences were found in UBH and SEBT assessments. During the SLS task, trail runners exhibited less ankle varus and less ankle external rotation at peak knee flexion in comparison to road runners. These findings suggest that trail runners’ performance in the SLS test may represent a kinematic adaptation to habitual terrain targeted at minimising ankle joint movement during weight-bearing. Subsequently, we aimed to determine whether running biomechanics would differ between 20 habitually shod trail runners and 20 road running counterparts due to their preferred training terrain. A special focus of this chapter was to determine whether the groups of runners presented with disparate risk of sustaining a running-related injury (RRI). To evaluate this hypothesis, all runners performed barefoot and shod overground running trials on a synthetic track. Regardless of footwear condition, trail runners presented with greater step frequency, shorter ground contact time and shorter step duration. Further group differences were observed, with trail contact time and shorter step duration. Further group differences were observed, with trail runners exhibiting notably advantageous kinematics at the level of the ankle and the foot, presenting with: smaller foot strike angle, lower pronation magnitude and velocity, and lower ankle stiffness. Considering these biomechanical parameters, it was unexpected to find that trail runners experienced similar initial loading rates (ILRs) and higher ground reaction forces to road runners in response to the synthetic track. The final experimental chapter explored the notion that preferred running terrain has an influence on neuromuscular regulation of running biomechanics. To examine this, electromyography and biomechanical variables were determined using previously described protocols. Regardless of footwear condition, trail runners exhibited greater gluteus maximus, biceps femoris and peroneus longus muscle activation during terminal swing in comparison to road runners. In addition, trail runners exhibited greater tibialis anterior activation during early swing. With regards to discrete biomechanics, trail runners presented with greater lower extremity joint stability in the sagittal plane, demonstrating lower pelvic, hip and knee flexion at initial ground contact. Interestingly, similar ground reaction forces were experienced by trail and road runners on the synthetic track, suggesting that the observed muscle 'tuning’ responses to these impact forces may be managed by the differing neuromuscular responses. The outcomes of this thesis suggest that there are numerous clinical, mechanical and neuromuscular implications of habitual running training on the trail and road. Although the present thesis is the first step to understanding the demands of regular trail running on the human body, future studies using portable motion capture and inertial systems are necessary to determine the precise influence of real-time trail running on the neuromuscular system and running biomechanics. Interestingly, trail runners demonstrated several purported 'advantageous’ kinematic and spatiotemporal parameters, and exhibited differing muscle activity patterns in comparison to road runners in a controlled laboratory setting. However, trail and road runners experienced similar ILRs in response to the synthetic track. Considering the high incidence of road RRI, and that higher vertical load has been associated with chronic RRI, this finding suggests that trail and road runners could be at similar risk of developing a RRI. However, due to the disparate nature of trail and road running terrains and the multifactorial nature of RRIs, further clarity on 1) the acute and long-term effects of off-road running and 2) the injury risk profile of a trail runner, is imperative for a holistic understanding of the risks and benefits associated with participation in this sport. We recommend that the influence of trail running on the musculoskeletal system presented in this thesis be considered as a foundation for future large-scale epidemiological and prospective injury research.